Efficacy and safety of immune checkpoint inhibitors combined with chemotherapy as first-line treatment for extensive-stage small cell lung cancer: a meta-analysis based on mixed-effect models - Zheng, Jianqing; Deng, Yujie; Huang, Bifen; Chen, Xiaohui (Frontiers in Medicine, 2023)
Background: Extensive-stage small cell lung cancer (ES-SCLC) is a highly invasive and fatal disease with limited therapeutic options and poor prognosis decades ago. Our study is to systematically evaluate the efficacy and safety of immune checkpoint inhibitors combined with chemotherapy (ICIs+ChT) versus chemotherapy alone (ChT) in the first-line treatment of ES-SCLC.Methods: A literature search was performed for randomized controlled trials (RCTs) related to "ICIs+ChT" versus "ChT" in the first-line treatment of ES-SCLC in PubMed, Cochrane Library, Embase, CNKI and other databases. RevMan 5.4 software was used to perform meta-analyses with hazard ratio (HR) and relative risk (RR). SAS 9.4 software was applied to conduct a mixed-effects model meta-analyses of the survival outcomes and draw survival curves.Results: A total of 2638 patients with ES-SCLC from 6 RCTs were included, of which 1341 patients received "ICIs+ChT" and 1297 received ChT. Based on the meta-analysis results provided by the mixed-effects model, patients receiving "ICIs+ChT" regimen had a significantly longer overall survival (OS, HR=0.800, 95% CI=0.731-0.876, P <0.001) and progression-free survival (PFS, HR=0.815, 95% CI=0.757-0.878, P <0.001) in comparison to those receiving ChT only. Compared with ChT, "ICIs+ChT" did not improve the objective response rate (ORR, RR=1.06, 95%CI=1.00-1.12, P=0.06), nor did it improve the disease control rate (DCR, RR=0.97, 95%CI=0.92-1.03, P=0.35).Although the incidence of grade 3 to 5 treatment-related adverse events (trAEs) in "ICIs+ChT" subgroup did not increase (RR=1. 16, P=0.11), the incidence of grade 3 to 5 immune-related adverse events (irAEs) increased significantly (RR=4.29, 95%CI=1.73-10.61, P<0.00001).ICIs+ChT regimen could significantly prolong OS and PFS in patients with ES-SCLC compared with ChT alone. Although the incidence of irAEs in "ICIs+ChT" is higher than that in "ChT" subgroup, the incidence of trAEs is similar within 2 subgroups. ICIs combined with chemotherapy demonstrated a good choice as first-line treatment for ES-SCLC.